The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1371/journal.pone.0136901
|View full text |Cite
|
Sign up to set email alerts
|

Transient Receptor Potential Vanilloid 2 Regulates Myocardial Response to Exercise

Abstract: The myocardial response to exercise is an adaptive mechanism that permits the heart to maintain cardiac output via improved cardiac function and development of hypertrophy. There are many overlapping mechanisms via which this occurs with calcium handling being a crucial component of this process. Our laboratory has previously found that the stretch sensitive TRPV2 channels are active regulators of calcium handling and cardiac function under baseline conditions based on our observations that TRPV2-KO mice have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 28 publications
(49 reference statements)
1
11
0
Order By: Relevance
“…Our data support previous reports regarding the mildly-attenuated cardiac performance in TRPV2-KO mice compared to their WT counterparts [ 15 , 16 ]. Moreover, Katanosaka and his colleagues have recently reported that heart-specific elimination of TRPV2 may be critically detrimental to cardiac structure and function in mice [ 29 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our data support previous reports regarding the mildly-attenuated cardiac performance in TRPV2-KO mice compared to their WT counterparts [ 15 , 16 ]. Moreover, Katanosaka and his colleagues have recently reported that heart-specific elimination of TRPV2 may be critically detrimental to cardiac structure and function in mice [ 29 ].…”
Section: Discussionsupporting
confidence: 93%
“…First, we wished to analyze whether TRPV2-WT and TRPV2-KO animals demonstrate any differences in cardiac function as previously suggested [ 15 , 16 ]. To this end, TRPV2-WT and KO male mice aged 12–16 weeks (6/arm) were studied by echocardiography.…”
Section: Resultsmentioning
confidence: 99%
“…M-mode measurements of the LV end diastolic dimension (LVEDD) and LV end systolic dimension (LVESD), posterior and anterior wall thickness and ejection time, measured at end diastole, were calculated from original tracings by employing a commercially available image analysis system (Freeland Medical, Alpharetta, GA, USA). 41…”
Section: Generation Of Recombinant Proteins and Blot-overlay Assaymentioning
confidence: 99%
“…Although TRPV1 −/− mouse skeletal muscles have never been phenotyped before our investigation, other members of the TRPV family had. Naticchioni et al reported that the contractile function of skeletal muscles was unchanged in TRPV2 null mice [ 45 ]. Similarly, lack of TRPV4 did not cause any alteration of muscular force production or fatigue [ 46 ].…”
Section: Discussionmentioning
confidence: 99%